Design and Architecture of an Open Multiplayer Exergaming Platform called Move2Play - Coutinho, Flávio; Silva, Ismael; Barbosa, Glívia; Costa, Thiago; Carvalho, Luis; Andrade, Cassiano; Pereira, João; Pinto, Reynaldo; Silva, Jonathan (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais do XXI Simpósio Brasileiro de Jogos e Entretenimento Digital, 2022)
Exergaming has been shown to increase the interest in regular physical activity. However, the available options usually involve acquiring specialized hardware, may be tied to a single game, and are generally designed for single player. A gym environment, for example, could benefit from not having to acquire adhoc and expensive hardware for each user. In this scenario, we propose Move2Play, an exergaming platform that relies on commodity hardware - a computer, a screen, and one smartphone per player - to offer single and multiplayer game sessions. In addition, the platform is extensible to new games, which third parties can produce. Also, four toy exergames were developed for demonstration. We believe that Move2Play can foster the practice of physical activities and contribute to promoting health and well-being.